Prevalence of Vitamin B12 Deficiency in Patients Treated With Metformin - Peixoto, Bruno Daniel Oliveira; Gonçalves, Mariana Abreu; da Costa, Ana Isabel Ferreira; Gonçalves, Teresa Filipa Ramôa (Scripta Medica, 2024)
Background/aim: Metformin has been associated with vitamin B12 (cobalamin) deficiency, pushing scientific societies such as the American Diabetes Association and the European Association for the Study of Diabetes to emphasise the need for screening B12 levels, without specific metformin doses or exposure durations triggering this screening. Robust data regarding the prevalence of B12 deficiency in metformin-treated patients in Portugal are currently lacking. Aim of this study was to identify the prevalence of B12 deficiency in a sample of diabetic patients taking metformin. Secondary objectives were determining the minimum dose and minimum and median time exposure time leading to this deficiency and identifying the average duration of metformin use in the patients with this deficiency.Methods: Descriptive and cross-sectional observational study was performed on a sample of 79 users from a population of 714 diabetic patients on metformin. Inclusion criteria comprised individuals aged 18 or older, receiving metformin for at least 1 month and voluntarily participating in the study. Exclusion criteria included a history of gastrectomy or B12 supplementation.Results: A prevalence of 25.3 % of vitamin B12 deficiency was identified in the study sample. Minimum doses of 500 mg of metformin per day and a minimum exposure period of 1 year were associated with B12 deficiency. An average exposure time of 5.33 years was identified. Conclusion: These results align with the prevalence described in the few international studies and should alert physicians to potential clinical manifestations of this deficiency, such as anaemia and neurological symptoms like neuropathy.